Boundaries of word-formation. New reflections on old things - Smetona, Antanas (Lietuvių kalba, 2020)
The attitude that word-formation fully coincides with derivation has been well established in the Lithuanian linguistics. The means of formation that fall outside derivation are regarded as peripheries of derivation that are not worth a considerable attention, although formal features of derivation are obvious (skruzdėlė cf. skruzdė), or absolutely fruitless prescriptive discussions about some kind of mistakes (profsąjunga cf. vyrgydytojas) are generated. In addition, composition is attributed to derivation, even when it is not clear where word-formation formant is and how to identify the meaning of forming a compound (nelaižytveršis: nelaižytas veršis). The article puts forward a solution to the discussed problems, which embraces all the formation in the Lithuanian language (not only derivation) and deals with the problems of derivation mentioned here.Seeking to address the problems raised, it is necessary to evaluate the role of language economy in the word-formation and, based on this evaluation, to expand perception of the importance of word-formation. Word-formation embraces not only derivation, but also all other ways of formation that go beyond the boundaries of morphemes. However auxiliary, insignificant or peripheral they may seem, they are a part of an integral word-formation system. All the attributes of this word-formation phenomenon, such as opposition, foundation and formant, synchronically apply to the whole word-formation. For this reason, the boundaries of derivation should be expanded. The most significant question here refers to semantic measuring and the volume of the formation meaning. Taking into account the fact that the main and fully comprehensive function of word-formation is not about increasing the number of words, but rather about rationalisation of their emergence, i.e. language economy, and also assuming that all the aspects of formation meaning (lexical, grammatical as well as economy) overlap and only one of them prevails, the general scheme of formation meaning (not only the derivational meaning) can be presented more or less as follows:Meaning of economy (profsąjunga, mikriukas, epaštas, JT, sodra, nelaižytveršis, eras, skruzdė) economizing means of linguistic expression.Grammatical meaning (gerumas, ėjimas, begalvis, palangė, stiklinė) change in grammatical content economizing means of linguistic expression.   Lexical meaning (žiūrovas, namelis, įlanka, snūduriuoti, rugiagėlė, nueiti) change in lexical content economizing means of linguistic expression and changing grammatical content if necessary.Such explanation of the general meaning of formation and inclusion of language economy expands the understanding of formation beyond the boundaries of derivation and allows referring to a new concept of the word-formation system.
Keywords: word formation; derivation; composition; formant; grammatical meaning; lexical meaning; language economy